Autoreactive T cells specific for insulin B:11-23 recognize a low-affinity peptide register in human subjects with autoimmune diabetes - Yang, Junbao; Chow, I-Ting; Sosinowski, Tomasz; Torres-Chinn, Nadia; Greenbaum, Carla J; James, Eddie A; Kappler, John W; Davidson, Howard W; Kwok, William W (Proceedings of the National Academy of Sciences - PNAS, 2014)
Previous studies in type 1 diabetes (T1D) in the nonobese diabetic mouse demonstrated that a crucial insulin epitope (B:9-23) is presented to diabetogenic CD4 T cells by IA(g7) in a weakly bound register. The importance of antigenic peptides with low-affinity HLA binding in human autoimmune disease remains less clear. The objective of this study was to investigate T-cell responses to a low-affinity self-epitope in subjects with T1D. HLA-DQ8 tetramers loaded with a modified insulin peptide designed to improve binding the low-affinity register were used to visualize T-cell responses following in vitro stimulation. Positive responses were only detectable in T1D patients. Because the immunogenic register of B:9-23 presented by DQ8 has not been conclusively demonstrated, T-cell assays using substituted peptides and DQ8 constructs engineered to express and present B:9-23 in fixed binding registers were used to determine the immunogenic register of this peptide. Tetramer-positive T-cell clones isolated from T1D subjects that responded to stimulation by B:11-23 peptide and denatured insulin protein were conclusively shown to recognize B:11-23 bound to HLA-DQ8 in the low-affinity register 3. These T cells also responded to homologous peptides derived from microbial antigens, suggesting that their initial priming could occur via molecular mimicry. These results are in accord with prior observations from the nonobese diabetic mouse model, suggesting a mechanism shared by mouse and man through which T cells that recognize a weakly bound peptide can circumvent tolerance mechanisms and play a role in the initiation of autoimmune diseases, such as T1D.